2016
DOI: 10.1016/j.jnci.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Results of treatment of lymphoblastic lymphoma at the children cancer hospital Egypt – A single center experience

Abstract: Introduction Lymphoblastic lymphoma (LBL) and acute lymphoblastic leukemia (ALL) are neoplasms of immature B or T-cell precursors. They are considered as a unique biological entity in the 2008 World Health Organization Classification of Hematologic Neoplasm. Both entities are arbitrarily separated by a cut-off point of 20-25% of blast cells in the bone marrow. Treatment of LBL has evolved over time from conventional high-grade NHL schedules to ALL-derived protocols. The aim of this work is to report the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Acute lymphoblastic leukemia (ALL) results in the malignant proliferation of lymphoid precursor cells of the bone marrow [1, 2] and is the most common cause of pediatric malignancy including 25% of all cancers in children [3]. It has been shown that prognosis would be dependent on the genetic characteristics of ALL, patient's age, the white cell account, clinical status, and the function of major organs.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lymphoblastic leukemia (ALL) results in the malignant proliferation of lymphoid precursor cells of the bone marrow [1, 2] and is the most common cause of pediatric malignancy including 25% of all cancers in children [3]. It has been shown that prognosis would be dependent on the genetic characteristics of ALL, patient's age, the white cell account, clinical status, and the function of major organs.…”
Section: Introductionmentioning
confidence: 99%